A comparative analysis of the G1/S transition control in kinetic models of the eukaryotic cell cycle - Conradie, Riaan (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2009.